Comparison of Ganglion Cell and Retinal Nerve Fiber Layer Thickness in Pigment Dispersion Syndrome, Pigmentary Glaucoma, and Healthy Subjects with Spectral-domain OCT. (4th March 2017) - Arifoglu, Hasan Basri; Simavli, Huseyin; Midillioglu, Inci; Berk Ergun, Sule; Simsek, Saban
Abstract: Purpose : To evaluate the ganglion cell complex (GCC) and retinal nerve fiber layer (RNFL) thickness in pigment dispersion syndrome (PDS) and pigmentary glaucoma (PG) with RTVue spectral domain optical coherence tomography (SD-OCT). Methods : A total of 102 subjects were enrolled: 29 with PDS, 18 with PG, and 55 normal subjects. Full ophthalmic examination including visual field analysis was performed. SD-OCT was used to analyze GCC superior, GCC inferior, and average RNFL thickness. To compare the discrimination capabilities, the areas under the receiver operating characteristic curves were assessed. Results : Superior GCC, inferior GCC, and RNFL thickness values of patients with PG were statistically signicantly lower than those of patients with PDS ( p  < 0.001) and healthy individuals ( p  < 0.001 for all). No statistically significant difference was found between PDS and normal subjects in same parameters ( p  > 0.05). Conclusions : The SD-OCT-derived GCC and RNFL thickness parameters can be useful to discriminate PG from both PDS and normal subjects.